Integrating PhET Interactive Simulation to Enhance Students' Mathematical Understanding and Engagement in Learning Mixed Fraction - Slamet Arifin; Fazilah Binti Razali; Winanjar Rahayu (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
AbstractThis study aims to document how integrating PhET interactive simulations into mathematics learning enhances students' conceptual understanding of mixed fraction material. This collaborative action research project adhered to the action research cycle proposed by Kemmis and McTaggart. In total 17 4th-grade students from one of the public elementary schools in Malang City, Indonesia participated in this investigation. The data was collected through tests, interviews, and classroom observation. The test of students' mathematical understanding (TSMU) was administered to the students at the pre-cycle, post-cycle I, and post-cycle II stages. The number of questions given in each test was 10 mathematical problems, and they were designed to assess students' mathematical understanding of mixed fractions. The quantitative data was analyzed by using descriptive statistics using SPSS 25, and the qualitative data was analyzed simultaneously using a qualitative data analysis cycle. The research findings unveiled the following key insights. First, we found a notable enhancement in students' mathematical understanding of mixed fractions emerged throughout the study. Specifically, the pre-cycle average score for students' mathematical understanding stood at M=51.59, which saw substantial improvement in the post-cycle I phase (M=61.53) and further growth in the post-cycle II phase (M=76.94). Moreover, the utilization of PhET simulations was found to significantly enhance students' engagement in the realm of mathematics learning. Therefore, the integration of PhET interactive simulation in mathematics learning has been shown to have a significant effect on improving students' mathematical understanding and engagement in learning fractions.Keywords: PhET interactive simulation, conceptual understanding, mixed fractions, students’ engagement. AbstrakPenelitian ini bertujuan untuk mendokumentasikan bagaimana integrasi PhET interactive simulation ke dalam pembelajaran matematika meningkatkan pemahaman konseptual siswa pada materi pecahan campuran. Desain penelitian tindakan kelas kolaboratif (PTK) dilaksanakan mengikuti siklus penelitian tindakan Kemmis dan McTaggart. Sebanyak 17 siswa kelas 4 di salah satu sekolah dasar negeri di Kota Malang, Indonesia dilibatkan dalam penelitian ini. Pengumpulan data dilakukan melalui tes, wawancara, dan observasi kelas. Tes pemahaman matematis siswa (TPMS) diberikan kepada siswa pada tahap pra siklus, pasca siklus I, dan pasca siklus II. Jumlah soal yang diberikan dalam setiap tes adalah 10 soal matematika, dan dirancang untuk menilai pemahaman matematis siswa tentang pecahan campuran. Data kuantitatif dianalisis dengan menggunakan statistik deskriptif menggunakan SPSS 25, dan data kualitatif dianalisis secara simultan mengacu pada siklus analisis data kualitatif. Hasil penelitian mengungkapkan bahwa: (1) terdapat peningkatan kemampuan pemahaman matematis siswa pada materi pecahan campuran. Hasl ini ditunjukan dengan rata-rata hasil TPMS pada pra-siklus M=51,59, pasca siklus I M=61,53, dan pasca siklus II M=76,94; (2) penggunaan PhET interactive simulation terbukti berkontribusi dalam meningkatkan keterlibatan siswa dalam pembelajaran matematika. Oleh karena itu, integrasi simulasi interaktif PhET dalam pembelajaran matematika terbukti memberikan pengaruh yang signifikan terhadap peningkatan pemahaman konsep matematis pecahan campuran siswa.Keywords: PhET interactive simulation, pemahaman matematis, pecahan campuran, keterlibatan siswa.